1993
DOI: 10.1002/bies.950150406
|View full text |Cite
|
Sign up to set email alerts
|

Early human embryo metabolism

Abstract: Non-invasive microanalytical methods have been devised to study the energy metabolism of single human preimplantation embryos. Pyruvate, which is added routinely to all media used to culture human embryos, is consumed throughout the preimplantation period, with glucose assuming an increasing role at embryo compaction and blastocyst formation. All of the glucose consumed may be accounted for by the appearance of lactate in the incubation medium. The enzyme hexokinase may be involved in regulating this aerobic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 41 publications
1
61
0
1
Order By: Relevance
“…Pyruvate, lactate, lipids and amino acids are present in the oviductal fluid, and the levels of these nutrients fluctuate through the estrous cycle in mice, rabbits, pigs and humans (Nieder & Corder 1982, Nichol et al 1992, Leese et al 1993, Tay et al 1997. The carboxylic acids are processed through immature mitochondria (characterized by the short and less formed cristae, shown in Fig.…”
Section: Nutrientsmentioning
confidence: 99%
“…Pyruvate, lactate, lipids and amino acids are present in the oviductal fluid, and the levels of these nutrients fluctuate through the estrous cycle in mice, rabbits, pigs and humans (Nieder & Corder 1982, Nichol et al 1992, Leese et al 1993, Tay et al 1997. The carboxylic acids are processed through immature mitochondria (characterized by the short and less formed cristae, shown in Fig.…”
Section: Nutrientsmentioning
confidence: 99%
“…It stands to reason that cancer cells derived from certain tissues might retain some of the metabolic profiles of that tissue, depending on how undifferentiated the cancer cells are. Note that early stage mammalian embryos utilize both aerobic glycolysis and glutaminolysis, 19,20 suggesting that cancer cells that are highly reviewed in reference 12, well before a link between glycolysis or glutamine metabolism with oncogenes or tumor suppressors was established. The first direct mechanistic link between an oncogene and altered cancer cell metabolism was documented in 1997 via the activation of the lactate dehydrogenase A (LDHA) gene by the Myc oncogenic transcription factor, 13 which was later shown to regulate virtually all glycolytic enzymes including the glucose transporter Glut1.…”
Section: Glutaminolysismentioning
confidence: 99%
“…Also, its uptake decreases after eight-cell stage while an increase on glucose uptake is observed [27]. Although some authors [28] suggested that the presence of glucose might compromise the viability of embryo development in vitro, our results corroborate the findings of Barak et al [29] and Macklon et al [30], that demonstrated that glucose does not necessarily inhibit early embryo development, as both culture media used in the our study had glucose in its composition, and good quality embryos were similarly obtained in all groups.…”
Section: Discussionmentioning
confidence: 95%
“…Concerning energy pathways, it has been demonstrated that from zygote to eight-cell stage, pyruvate is the main source used by the embryo to produce ATP [25][26][27]. Also, its uptake decreases after eight-cell stage while an increase on glucose uptake is observed [27].…”
Section: Discussionmentioning
confidence: 99%